Effects of repetitive transcranial magnetic stimulation (rtms) treatment in comorbid nicotine addiction with major depressive disorder and obsessive-compulsive disorder - Yaşar, Asena Uzdu; Cinemre, Buket; Erdoğan, Ali (Journal of Dependence, 2022)
Objective: Nicotine addiction is a common health problem in psychiatric disorders. The aim of this study was to analyze the effects of rTMS on comorbid nicotine addiction in patients receiving recurrent Transcranial Magnetic Stimulation (rTMS) therapy for major depressive disorder (MDD) and obsessive-compulsive disorder (OCD).Method: Data of 32 patients (23 MDD, 9 OCD) were evaluated retrospectively. We compared the Hamilton Depression Rating Scale (HAM-D), Beck Anxiety Inventory (BAS), Yale-Brown Obsession Compulsion Scale (Y-BOCS), and Fagerström Test for Nicotine Dependence (FTND) scores at three time points (before treatment “0th week”, at the end of treatment “6th week”, and 12 weeks after this assessment “18th week”).Results: The patients’ mean age was 40.47±10.20, 13 (40.6%) were women. A significant reduction was found in HAM-D, BAS, FTND at weeks 6 (p
Keywords: Neuromodulation; nicotine addiction; psychiatric disorders; transcranial magnetic stimulation; rTMS